2021
DOI: 10.1186/s12879-021-06681-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous N-acetylcysteine in acute severe hepatitis due to severe dengue infection: a case series

Abstract: Background Dengue fever is a common mosquito borne viral infection. Severe dengue fever associated severe hepatitis carries high mortality. Based on the beneficial effect of N-acetylcysteine (NAC) in paracetamol poisoning and non-acetaminophen induced liver failure, it is used in dengue fever associated hepatitis in clinical practice. We aim to study the reversal of liver enzymes with NAC in the setting of severe hepatitis due to severe dengue infection. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
(44 reference statements)
0
8
0
2
Order By: Relevance
“…Deterioration of severe acute HBV infection to ALF was prevented in 22 of the 24 cases (92%). These patients could be discharged after median (range) 12 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days following initiation of the antiviral drug. Median (range) maximum ALT, total bilirubin and INR levels were as follows: 2534 (1176-5679) U/L, 17 (10-38) mg/dL and 1.7 (1.4-3.2); median(interquartile range) viral load was 63 000 (23 600-3 680 000) copies/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deterioration of severe acute HBV infection to ALF was prevented in 22 of the 24 cases (92%). These patients could be discharged after median (range) 12 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days following initiation of the antiviral drug. Median (range) maximum ALT, total bilirubin and INR levels were as follows: 2534 (1176-5679) U/L, 17 (10-38) mg/dL and 1.7 (1.4-3.2); median(interquartile range) viral load was 63 000 (23 600-3 680 000) copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, this evolved to a standard protocol for all patients: 100 mg/kg/day NAC for 72 h, lactulose at a dose titrated to achieve 2-3 defecations per day and 15 mg/kg/ day ursodeoxycholic acid to all patients without vomiting. Although the initially suggested role of NAC in early stage non-acetaminophen ALF [12] has not been confirmed in randomized trials [13], the absence of an obvious negative effect [13] and encouraging reports on its effects in acute-on-chronic hepatitis B [14], as well as hepatitis due to other hepatotropic viruses [15][16][17], led to its inclusion in the standard protocol.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Management of ALF in dengue infection is largely supportive in an intensive care setting. Some of the centers have used NAC in adults with variable results but it is not part of our management protocol and its use was sporadic (21,22). We did not find any significant difference in survival with the use of NAC though Sriphongphankul et al (16) from Thailand found it to be beneficial in dengue PALF.…”
Section: Discussionmentioning
confidence: 99%
“…Tal dano ocorre em pacientes com dengue e isso se deve à toxicidade viral ou por uma resposta imune desregulada ao vírus. Normalmente, promove alterações nos marcadores bioquímicos, principalmente, o aspartato aminotransferase (AST) e a alanina aminotransferase (ALT), alterações observadas, inclusive, em pacientes assintomáticos (Cesar;Piloto, 2015;Wan et al, 2018;Seneviratne, 2018;Tafere;Wondafrash;Demoz, 2020;Dissanayake et al, 2021).…”
Section: Alterações Hepáticas Decorrentes Da Dengue E Do Uso Do Parac...unclassified